Modified Optimization Analysis based on Gear System Meshing Misalignment - Xin Zhang; Xinrong Liu (Jixie chuandong)
Considering the support deformation of the gearbox，shafting and the thermal deformation of gear transmission system，the amount of gear meshing misalignment is calculated. Force analysis of the gearbox is carried out by finite-element software，the contact analysis of gear pair is carried out，gear shaft displacement is calculated by mechanics principle and finite-element node method，the thermal deformation of the profile contact line is calculated，and the change of contact displacement of gear profile by finite-element thermoelastic coupling is analyzed. The gear is modified and optimized，the experimental results are compared. The results show that the gear system meshing dislocation is the comprehensive effect of the deformation of each part； the gear modification optimization can help to reduce the gear system meshing misalignment，the gear shaft offset and the gear transmission error，and improve the stability and reliability of gear transmission.